STRATEGI ADAPTASI IKLIM UNI EROPA DI TENGAH TANTANGAN PERANG RUSIA-UKRAINA TAHUN 2022 - Agus Nilmada Azmi; Siti Zulhaiziah Azalea Zahfira (Emerald: Journal of Economics and Social Sciences, 2024)
The Russia-Ukraine war of 2022 presents a significant challenge to the European Union's (EU) climate adaptation strategy. This article examines the implications of war on the EU's efforts to tackle climate change and highlights the need to achieve a sustainable energy security balance. This shift in coal use has a detrimental effect on climate adaptation and exacerbates the EU's vulnerability to climate change. To address these issues, the EU must redouble its efforts to prevent new security risks, seek sustainable energy alternatives, and strengthen international partnerships to support other countries in the energy transition. By taking these steps, the EU can navigate the complex landscape of energy security and sustainability while working to achieve its climate adaptation goals.